DETECTION OF AFLATOXINS IN AMBULATORY SAMPLES OF CANNABIS OIL SOLUTION FROM LIMA METROPOLITANA BY FLUORESCENCE LIQUID CHROMATOGRAPHY DETECTOR (FL-HPLC) - Castro Luna, Américo (2025)
In this study we identified and quantified five samples of oily solutions of cannabis that were collected on an outpatient basis from the center of Lima, Perú, in order to perform the analysis was performed by liquid chromatography with fluorescence detector (HPLC-FL) analysis required a standard containing a mix of four aflatoxins which are aflatoxins G1, B1, G2 and B2, From the standard aflatoxins of a concentration of 2,6 ug/mL (mix of AFB1, AFB2, AFG1 and AFG2) 1ug/mL of AFB1, 1ug/mL of AFG1, 0. 3 ug/mL of AFB2 and 0.3 ug/mL of AFG2, the results obtained in the analyzed samples do not contain aflatoxins. Quality control is of utmost importance to verify that the formulations with cannabis can have an adequate dose, the adequate dose, contamination by microorganisms, mycotoxins such as aflatoxins, pesticides, among others, must be controlled in order to avoid dangerous consequences for health, safety standards and the respective quality control must be complied with.